A comparative characterization of defect structure in NiCo and NiFe equimolar solid solution alloys under in situ electron irradiation. (June 2019) - He, Mo-Rigen; Wang, Shuai; Jin, Ke; Bei, Hongbin; Yasuda, Kazuhiro; Matsumura, Syo; Higashida, Kenji; Robertson, Ian M.
Abstract: Dislocation loops in NiCo and NiFe, both being single-phase, equimolar solid solution alloys, are generated by in situ high-voltage electron irradiation and characterized inside a transmission electron microscope. In addition to the different defect growth rates, the two alloys present dislocation loops with distinct shape evolution and element segregation, which reflect the element-sensitive, intrinsic properties (e.g., defect energetics, lattice distortion, and local ordering) of the alloys. These results provide evidence that the structure and dynamics of radiation-induced defects in concentrated alloys depend on not only the number but also the species of alloying elements. Graphical abstract: Unlabelled Image